2009
DOI: 10.1159/000199468
|View full text |Cite
|
Sign up to set email alerts
|

Criteria for a Clinically Informative Serum Biomarker in Acute Ischaemic Stroke: A Review of S100B

Abstract: Background and Purpose: Serum S100B has been widely studied as a biomarker in acute ischaemic stroke. The main objective of this review was to appraise the published literature on S100B and determine its clinical applicability. Methods: Medline was searched to identify studies on S100B (or S-100B) in acute ischaemic stroke. The authors have proposed the criteria for a clinically informative serum biomarker for acute ischaemic stroke, and relevant articles relating to these criteria were then selected. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 72 publications
3
59
0
6
Order By: Relevance
“…Concentrations in cerebrospinal fluid (CSF) were found to be up to 60 times higher than in serum [5]. Importantly, previous reports indicated that S100B serum values correlate with final infarct volume when determined beyond 24 h after symptom onset [6][7][8]. In contrast to the multiple sources of S100B, neurofilaments, a group of proteins integrated into the scaffolding of the neuronal and axonal cytoskeleton, are specific to and abundant in the neuro-axonal compartment [9].…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations in cerebrospinal fluid (CSF) were found to be up to 60 times higher than in serum [5]. Importantly, previous reports indicated that S100B serum values correlate with final infarct volume when determined beyond 24 h after symptom onset [6][7][8]. In contrast to the multiple sources of S100B, neurofilaments, a group of proteins integrated into the scaffolding of the neuronal and axonal cytoskeleton, are specific to and abundant in the neuro-axonal compartment [9].…”
Section: Introductionmentioning
confidence: 99%
“…The timing of blood withdrawal in relation to symptom onset can also introduce variability in the sensitivity reported in different studies. The lower specificity reported is probably due to the fact that it was defined by other authors as a 95% or 98% reference interval in subjects without disease, 12 while our values were calculated on the basis of stroke mimics and for control subjects with a high prevalence of hypertension.…”
Section: Discussionmentioning
confidence: 82%
“…There are several reports indicating that both proteins are markers of glial and neuronal injury in ischaemic stroke and a smaller number of studies demonstrating the role of peripheral markers in haemorrhagic stroke. [9][10][11][12][13][14] However these markers are not specific for stroke; raised levels of NSE and S100B have also been found in other neurological conditions such as Alzheimer's disease, epilepsy, brain tumours, dementia, schizophrenia and CreutzfeldtJackob disease, among others. [15][16][17][18] The correlation observed between NSE and S100B levels in stroke patients supports its association with acute damage of glial and neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Although the specificity of serum S100B protein is too low to diagnose acute stroke and the occurrence of its peak specificity is always late which means serum S100B protein is not suitable for the diagnosis of acute stroke, S100B protein is still regarded as a potential research area in acute ischemic stroke. [27]…”
Section: Resultsmentioning
confidence: 99%